Papier en cage - Donzel-Gargand, Bernard (Mnémothèque Internationale des Sciences et Arts en Musique Électroacoustique, 1992)
Recording of Bernard Donzel-Gargand's Papier en cage. In relation to dance, photoelectric cells are installed in the choreographic space and allow the dancer to interpret sound events, to create his music in real time. SAMI (computerized musical assistance system) is used by linking MIDI of an eight-input intelligent Analog/Digital converter, and a user interface written in MAX. The sampled sounds are transmitted via MIDI to a Macintosh, then after transformation to a sound generator.